2008
DOI: 10.1536/ihj.49.13
|View full text |Cite
|
Sign up to set email alerts
|

<b>The Etiology of &lsquo;Smoker&rsquo;s Paradox&rsquo; in Acute Myocardial Infarction With Special Emphasis on the Association With Inflammation</b>

Abstract: SUMMARYDespite increased risk for coronary artery disease and acute myocardial infarction (AMI), prior studies have found that smokers with AMI have lower mortality rates than nonsmokers, a phenomenon often termed 'smoker's paradox'. The present study was designed to examine the etiology of 'smoker's paradox', especially with respect to the association with inflammation.The subjects included 528 consecutive AMI patients who were admitted within 24 hours of onset and underwent successful coronary intervention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 35 publications
4
28
0
Order By: Relevance
“…We assumed that preexisting hypertension might be protective in ACS patients in the short term despite its clearly established role in increasing the long-term risk for coronary artery disease. Similar paradoxes have been previously described for smokers [10] as well as for patients with obesity [11].…”
Section: Introductionsupporting
confidence: 87%
“…We assumed that preexisting hypertension might be protective in ACS patients in the short term despite its clearly established role in increasing the long-term risk for coronary artery disease. Similar paradoxes have been previously described for smokers [10] as well as for patients with obesity [11].…”
Section: Introductionsupporting
confidence: 87%
“…This effect is caused by various factors such as sympathetic activation and inflammation. 15,16) It has already been showed that passive smoking was linked to cardiovascular events, and in that study being a passive smoker was determined by interview alone.…”
Section: Discussionmentioning
confidence: 90%
“…Two types of EES were available for use in the study: Xience V TM (Abbott Vascular, Santa Clara, CA, USA; diameters of 2.50, 2.75, 3.00, and 3.50 mm and lengths of 8,12,15,23, and 28 mm) and Promus Element TM (Boston Scientific, Natick, MA, USA; diameters of 2.50, 2.75, 3.00 and 3.50 mm and lengths of 8,12,16,20,24, and 28 mm). When loading of dual antiplatelet drugs was necessary, patients received 300 mg…”
Section: Methodsmentioning
confidence: 99%
“…Some previous reports have shown that current smoking was not necessarily a risk factor for clinical events after PCI in the BMS era. 20,21) However, recent papers on interventional cardiology written after the emergence of DES showed that current smoking is an independent risk factor for stent thrombosis 22) and neoatherosclerosis, 23) which can be a cause of late catch-up restenosis after DES implantation. Our results strongly support comprehensive risk control including patient education as a means of improving clinical outcomes in high risk subsets even in the contemporary DES-PCI era.…”
Section: Nomura Et Almentioning
confidence: 99%